2022
DOI: 10.3390/ani12162149
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in the Use of Acoustic Signals to Coordinate Group Movements among Tibetan Macaques (Macaca thibetana)

Abstract: To maintain group cohesion, social animals need to coordinate their actions during group movements. Several species use vocalizations to communicate with each other during coordination. However, the process of vocal communication and its influence in collective decision making is not clear. We studied a group of free-range Tibetan macaques (Macaca thibetana) at Huangshan, China, and recorded acoustic signals during their group movements. It was found that three kinds of sounds were used in their movements. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In previous research, it was observed that females were more adept at using vocal communication to recruit a greater number of followers than males when initiating group movements. This proficiency in vocal signaling appeared to be a key factor in the higher follower recruitment by females, highlighting their important role in leading collective actions within the group [55]. A similar phenomenon was noted in Barbary macaques, further supporting this pattern of behavior [56].…”
Section: Individual Characteristics and The Initiator Of Group Movementssupporting
confidence: 63%
“…In previous research, it was observed that females were more adept at using vocal communication to recruit a greater number of followers than males when initiating group movements. This proficiency in vocal signaling appeared to be a key factor in the higher follower recruitment by females, highlighting their important role in leading collective actions within the group [55]. A similar phenomenon was noted in Barbary macaques, further supporting this pattern of behavior [56].…”
Section: Individual Characteristics and The Initiator Of Group Movementssupporting
confidence: 63%